2006
DOI: 10.1210/en.2006-0526
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Activator Protein-1 Proteins in the Pineal Gland of Syrian Hamster and Rat May Explain Species Diversity in Arylalkylamine N-Acetyltransferase Gene Expression

Abstract: Species differences have been reported for the nighttime regulation of arylalkylamine N-acetyltransferase (AA-NAT), the melatonin rhythm-generating enzyme. In particular, de novo synthesis of stimulatory transcription factors is required for Aa-nat transcription in the Syrian hamster but not in the rat pineal gland. The present work investigated the contribution of phosphorylated cAMP-responsive element-binding protein, c-FOS, c-JUN, and JUN-B in the regulation of Aa-nat transcription in Syrian hamsters compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…Therefore, the reduction in NFKB activation occurs before the lightdark transition in hamsters and is partially dependent on the increase in corticosterone level. These data reinforce that controlling the pineal nuclear activity is different in Syrian hamster and rats (Sinitskaya et al 2006).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Therefore, the reduction in NFKB activation occurs before the lightdark transition in hamsters and is partially dependent on the increase in corticosterone level. These data reinforce that controlling the pineal nuclear activity is different in Syrian hamster and rats (Sinitskaya et al 2006).…”
Section: Discussionsupporting
confidence: 81%
“…Melatonin synthesis is strongly restricted to the later part of the night in Syrian hamsters; however, the melatonin peak begins earlier in rats (Garidou et al 2003;Sinitskaya et al 2006). This melatonin synthesis delay in Syrian hamsters is attributed to noradrenaline inducing the clock gene Per1 at the beginning of darkness (Wongchitrat et al 2009), which blocks the transcription of key enzymes in melatonin synthesis (Christ et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Whether this is related to a difference in sensitivity between the AP-1 sites on the Aanat and Dio2 promoters toward the repressive effects of different Fra-2 complexes awaits further investigation. In this regard, it should be noted that JunB, which can form a repressive complex interacting with the AP-1 site, is also induced at night (41)(42)(43)(44), and it will be worthwhile to examine its contribution to the overall effect of the AP-1 complex on Dio2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we reported a fast NE‐driven induction of c‐Fos protein (9) and Icer mRNA (15) at night‐time in the Syrian hamster pineal gland. Moreover, both c ‐fos and Icer gene expression are subjected to the inhibitory action of ICER in other models: Icer (4, 16) and c ‐fos (17, 18).…”
mentioning
confidence: 92%
“…Recent studies, however, have pointed out that regulation of pineal Aa‐nat gene transcription varies among species (6, 7). In the Syrian hamster, CREB activation is not sufficient for Aa‐nat transcription at night because NE‐induced de novo synthesis of inducible TFs, in particular c‐Fos (8, 9), is also required. Moreover, adrenergic stimulation of Aa‐nat transcription and melatonin synthesis in the Syrian hamster is not possible during the light phase of the daily cycle (10–14).…”
mentioning
confidence: 99%